Rainwater chemical composition and annual atmospheric deposition in Sorocaba, (São Paulo state), Brazil - da Conceição, Fabiano Tomazini [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Angelucci, Vivian Andréia [UNESP]; Moruzzi, Rodrigo Braga [UNESP]; Navarro, Guillermo Rafael Beltran [UNESP] (Sociedade Brasileira de Geofisica, 2013)
This work evaluated the rainwater chemical composition and the annual atmospheric deposition in Sorocaba, (São Paulo State), Brazil. One sampling point was chosen and forty samples were collected between January and December 2006. The analyses were performed for pH, electrical conductivity, sodium, calcium, potassium, magnesium, sulphate, nitrate, phosphate, alkalinity and chloride. The rainwater pH varied from 5.20 to 6.40, being Ca2+ the main ion responsible for controlling the rainwater pH. The ionic concentration decreases in the following order: Ca2+>Na+>K+>Mg2+ for cations and SO2-4>HCO-3>NO-3>Cl->PO3-4 for anions. The annual atmospheric deposition appears to be controlled by the following sources: mining activities and cement factories (Ca2+ and HCO-3), agricultural activities (K+, NO-3 and PO3-4), soil dust (Na+, Mg2+ and HCO-3) and fossil fuel burning (SO2-4).
Keywords: Air pollution; Rainwater composition; Sorocaba